Evaluation of the Performance of an Ocular Surface Modulator Containing ST-Lysyal Versus Hyaluronic Acid Eyedrops in Patients with Dry Eye Disease: A Pilot Study - Stefano Barabino; Andrea Rosa; Sara Marini; Carlo Domenico Bianchi; Maurizio Rolando (Ophthalmology and Therapy, 2024)
Abstract Introduction Dry eye disease (DED) is a multifactorial condition of the ocular surface, primarily treated with tear substitutes, which do not fully restore natural tear functions. In this pilot study, we tested the hypothesis that T-Lysyal (T-Lys) improves symptoms and signs in patients with DED. Additionally, we provide a literature overview on the effects of T-Lys in ophthalmology and non-ophthalmology conditions to elucidate its mechanisms of action. Methods A double-masked, randomized pilot study was conducted in patients with DED treated with T-Lys or hyaluronic acid (HA) 0.2% combined with tamarind seeds polysaccharide (control group) for 2 months. Inclusion criteria were a diagnosis of DED with symptoms lasting ≥ 6 months, Symptom Assessment in Dry Eye (SANDE) score ≥ 30, and at least one of the following: fluorescein staining of the cornea (score ≥ 3, NEI scale), conjunctival staining (Lissamine Green, score ≥ 3), or tear breakup time (T-BUT) ≤ 10 s. Data from the right eye were used for statistical analysis. A PubMed literature search of T-Lys studies was also performed without publication year restrictions. Results Twelve patients in the T-Lys group and 15 in the control group completed the study (mean age 67 ± 11 years). T-Lys treatment resulted in significant improvements from baseline (V0) to 2 months (V2) in symptoms assessed by visual analogue scale (T-Lys: 4.58 ± 2.57 mm at V0, 2.92 ± 1.38 mm at V2, p < 0.05; control: 5.13 ± 2.29 mm at V0, 5.3 ± 2.4 mm at V2), T-BUT (T-Lys: 2.58 ± 1.31 s at V0, 3.58 ± 1.37 s at V2, p < 0.05; control: 3.07 ± 1.43 s at V0, 3 ± 1.13 s at V2), and corneal staining (T-Lys: 2.16 ± 4.17 at V0, 1.41 ± 3.70 at V2, p < 0.05; control: 1.4 ± 2.19 at V0, 1.4 ± 2.16 at V2). No adverse events were reported. Literature findings supported T-Lys’s efficacy in managing both ophthalmology and non-ophthalmology conditions. Conclusion This study provides the first clinical evidence of T-Lys efficacy in patients with DED, supporting preclinical data and highlighting its potential as a promising ocular surface modulator. Trial Registration The study was registered in the ISRCTN registry for Clinical Studies with no. 13587929.